2014
DOI: 10.1016/j.ypmed.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Communities putting prevention to work: Local evaluation of community-based strategies designed to make healthy living easier

Abstract: This introduction is an overview of the articles presented in this supplement that describe implementation and evaluation activities conducted as part of the Centers for Disease Control and Prevention’s (CDC’s) Communities Putting Prevention to Work (CPPW) initiative. CPPW was one of the largest federal investments ever to combat chronic diseases in the United States. CPPW supported high-impact, jurisdiction-wide policy, systems, and environmental changes to improve health by increasing access to physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Complementary to initiatives aimed at high-risk segments of the population are interventions that aim to change policies, systems, and environments, including priority-setting at the community and population levels. This reflects an awareness that end-stage treatment of chronic disease is not sufficient, and that there is a need to promote healthy lifestyles across the lifespan, and to address risk factors in multiple settings [58], including more deep seated health inequities based on high levels of income inequality. Notable examples are large scale development interventions aimed at broad societal change, such as the 'Prospera/ESIAN' Programme in Mexico [59] or the 'Zero Hunger/Academia Saúde Program' in Brazil [60,61].…”
Section: Community-based Initiativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary to initiatives aimed at high-risk segments of the population are interventions that aim to change policies, systems, and environments, including priority-setting at the community and population levels. This reflects an awareness that end-stage treatment of chronic disease is not sufficient, and that there is a need to promote healthy lifestyles across the lifespan, and to address risk factors in multiple settings [58], including more deep seated health inequities based on high levels of income inequality. Notable examples are large scale development interventions aimed at broad societal change, such as the 'Prospera/ESIAN' Programme in Mexico [59] or the 'Zero Hunger/Academia Saúde Program' in Brazil [60,61].…”
Section: Community-based Initiativesmentioning
confidence: 99%
“…There is positive evidence of programmes focused on components such as social marketing, stakeholder engagement, network and partnership development, community-directed needs PLOS ONE assessment and capacity building, showing changes in community capacity, but no or few impacts on individual knowledge, beliefs, perceptions and behaviour with relation to healthy eating, physical activity and sedentary lifestyle habits [34,51,54,58,62]. In contrast, some programmes-depending on their specific characteristics, including the number and duration of mutually reinforcing activities-show improvements in awareness, knowledge and behaviour indicators, but no measurable impacts at the community level, beyond the potential establishment of environmental conditions conducive to healthy behaviour [38,51].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, numerous policy, systems and environmental (PSE) change strategies have been implemented by public health authorities to combat this obesity epidemic [ 3 5 ]. These strategies have included interventions that were designed to assist individuals in losing or maintaining a normal weight through modifications of the food and the built environment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with the findings of other published evaluations of PSE-change initiatives. For example, Soler et al reported outcome evaluation findings from 6 PSE-change initiatives funded by CDC’s Communities Putting Prevention to Work program ( 27 ); most of these initiatives focused on changes to policies and environments ( 28 31 ), and none assessed changes in health behaviors or health outcomes. It is challenging to assess long-term changes resulting from PSE interventions when funding is typically limited to a few years.…”
Section: Discussionmentioning
confidence: 99%